Efektifitas Pembinaan Kader Kesehatan Remaja (KKR) tentang TRIAS UKS terhadap Upaya Pencegahan Kenakalan Remaja pada Siswa Tingkat SMA/MA - Muhammad Al Amin; Achmad efendi; Pipit Hariyono; Akhmad Yanuar Fahmi Pamungkas (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2019)
UKS is an education and health effort that is carried out in an integrated, conscious, planned, directed, and responsible manner in instilling, growing, developing, and guiding to live, enjoy, and implement the principles of healthy life in the lives of everyday students (Ahmad Selvia, 2009: 1). Based on the problems and research objectives to be achieved, this type of research is preexperimental research in the form of a